Bank finance for rural development / edited by L. K. Naidu - L.K. Naidu (ed.) (New Delhi, 1988)
The book attempts to provide a pers pective for extending bank finance for rural development in a developing economy like India. Beginning with early 70s, there has been a wide spread realisation regarding the need to repli cate the kind of structural transforma tion experienced by the developed world in the Third World as well. Bank Finance is considered as one of the factors which can bring about this transformation. The phenomenal growth of rural banking in recent times raises several important issues as the mobili zation and increased diversion of the rural deposits away from the rural sector. If it is so, to what extent it is desirable and possible to plough back the deposits for rural development? What strategies should the policy makers adopt in order to guarantee a certain minimum percentage of the bank credit for the weaker sections. What are the consequences of bracket ing those who have some resource (land) with those who have none ? How to combine a policy of non-secu rity but project-oriented lending policy with that of effective utilisation and repayment? The papers included in the volume emphasise the need for an cffective credit planning incorporating a right kind of credit-mix to various sub-groups of the weaker sections and nceded changes in credit delivery through banks as practiced in rural areas.
Keywords: Bank and banking